Remote health information systems for falls prevention in older adults at home: a scoping review - Dian Rizki Ramadhani; Alfiana Maulida Rahmah; Decky Nurhadi Sopyan; Novi Rohmawati; Putri Ramadhanti; Sali Zakiah Muslim (JHeS (Journal of Health Studies), 2025)
This review is to describe the remote health information system related to falls in the elderly used at home. We conducted a literature review using the Population Content Context (PCC) method. The databases used include EBSCOHost, Cochrane, and Scopus. The keywords used are (telehealth OR telemedicine OR telenursing OR m-health OR e-health) AND (elderly OR geriatric) AND falls AND home. The article selection process was done with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. As a result, 2.587 publications were identified and screened using the inclusion criteria. The assessment of article quality is conducted through assessment by design and manual assessment. The final result was 18 articles. The results of the article identification discussed the risk of falls, falls prevention, fall events, fear of falls, and response to falls with elderly respondents aged ≥ 55 years. So, there are various types of technologies used, namely sensor-based, phone calls, video conferencing, web, applications, force plates (style plates), tablet computers, smartphones, Artificial Intelligence (AI), and Virtual Reality (VR). The remote health information system has been proven to provide many benefits related to falls on the elderly at home.